PERSPECTIVES ON CHILD DEVELOPMENT FROM LINGUISTIC ASPECT - Achilova Gulhayo Ismailovna (Лучшие интеллектуальные исследования, 2023)
Abstract. In the past, scientists have looked at how children and parents naturally converse in order to understand how children grow. There were conducted number of interviews, over 140 talks between Katz and Katz's boys, who were 3 and 4 years old at the time of the initial recording, were gathered and studied in 1928. Katz [ 4]interpreted the conversation's substance to demonstrate "thinking, feeling and volitional attitudes taken up by the child towards his environment in general" as it emerges in the children's discourse. From the dialogue and their observations, they also tried to deduce the "character" of their kids analysis included.